The Pedicled Flap of Adductor Longus, a New Technique for Inguinal Reconstruction - Zhang, Hong; Li, Zhenfeng; Li, Jianmin; Zhu, Lei; Ibrahim, Yakubu (Frontiers in Surgery, 2021)
Abstract Introduction: Reconstruction surgeries of the inguinal area pose a challenge for oncological and orthopedic surgeons, especially after radical local resection (RLR), radical inguinal lymph node dissection (RILND) or both. Although numerous surgical procedures have been reported, there is no report about a pedicle adductor longus flap method. The aim of this work is to show our experience about inguinal reconstruction with pedicled adductor longus flap and associated outcomes. Patients and Methods: A retrospective study of 16 patients with localized inguinal region interventions and reconstructed by adductor longus flap from March, 2016 to July, 2020. Patients’ average age was 60.0 years (range= 38-79 years) and had postoperative follow-up of 10 months (ranging 2-19 months). All patients had unilateral inguinal region involvement- seven cases on the left and nine cases on the right. The patients’ clinical course, operative course, and postoperative follow-up data were evaluated. Results: All 16 patients recovered well post-operatively and did not require any re-intervention. Four patients experienced negligible discomfort around the groin area. Five patients experienced a minor strength deficit in thigh adduction, compared with that of preoperative strength in the same or contralateral leg. The aforementioned complications resolved during the postoperative course and had no functional impact on their activity of daily living. All adductor longus flaps survived, completely filled the inguinal dead space, and wounds healed uneventfully within three weeks except three patients who suffered delayed wound healing for more than four weeks. Other common complications such as infection, seroma, or wound dehiscence were not encountered in this series.. Conclusion: The adductor longus flap is a reliable alternative method for inguinal region reconstruction following radical local resection (RLR), radical inguinal lymph node dissection (RILND) or both.